The Role of Social Media in the Formation of Adolescent Identity: A Review of Psychology and Popular Culture - Budaraga, I Ketut (Journal of Dialogos, 2025)
Social media has become a fundamental element in the lives of modern adolescents, playing a significant role in the process of identity formation in the digital era. This study analyzes how social media platforms such as Instagram, TikTok, Twitter, and YouTube influence adolescent identity construction from the perspectives of developmental psychology and popular culture. Using a qualitative approach with a case study design, the study involved four adolescents aged 16-18 in Semarang City through in-depth interviews and observations of digital activities. The findings indicate that social media plays a dual role as a means of positive identity exploration and a source of psychological distress. Adolescents use digital platforms to experiment with various roles and lifestyles, but often become trapped in a false image to gain external validation. The process of identity formation is influenced by the dynamics of identity exploration and commitment, with social media providing a broad space for self-discovery but also creating the risk of identity conflict due to social comparison and popular cultural pressures. The study identified that adolescent girls are more vulnerable to negative impacts related to body image and beauty standards, while adolescent boys tend to focus on achievement and social recognition. Contextual factors such as family background, digital access, and local cultural values play a significant role in shaping adolescents' social media experiences. The results emphasize the need for structured digital literacy education and psychological support to help adolescents navigate the complexities of digital identity in a healthy and authentic manner.